Microsatellite variation in North American populations of Drosophila melanogaster. - Goldstein, D B (1995)
Computer database searching for microsatellites can be particularly effective for organisms like Drosophila melanogaster for which there are extensive sequence data. Here we demonstrate that 17 out of 18 such microsatellites are also highly polymorphic in natural populations of Drosophila, and that this variation is easily scorable with PCR followed by electrophoresis on high-resolution agarose. This form of variation is likely to be of great value in studies of the genomic distribution of polymorphism, population structure, the relation between intraspecific polymorphism and interspecific divergence and the mutation rate and pattern of mutations of microsatellites. In this preliminary survey of 15 lines, we find that the variance in repeat count is most strongly correlated with the maximum count, that perfect repeats are significantly more variable than imperfect repeats and that repeats which are split by an imperfection have unexpectedly low variance given the size of the perfectly repeated portion.